2022
DOI: 10.1128/msystems.00110-22
|View full text |Cite
|
Sign up to set email alerts
|

Multiplexed Strain Phenotyping Defines Consequences of Genetic Diversity in Mycobacterium tuberculosis for Infection and Vaccination Outcomes

Abstract: Tuberculosis, caused by the bacterium Mycobacterium tuberculosis , is a remarkably heterogeneous disease, a feature that complicates clinical care and public health interventions. The contributions of pathogen genetic diversity to this heterogeneity are uncertain, in part due to the challenges of experimentally manipulating M. tuberculosis , a slow-growing, biosafety level 3 organism.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…Further, since the drug tolerance spawned by heterogeneity is adaptive, we might anticipate that future work will demonstrate that the production of heterogeneous sub-populations is itself under genetic selection and control. In fact, multiple recent reports already point in that direction ( Bellerose et al., 2019 ; Safi et al., 2019 ; Safi et al., 2020 ; Ma et al., 2021 ; Carey et al., 2022 ; Martini et al., 2022 ).…”
Section: Discussionmentioning
confidence: 96%
“…Further, since the drug tolerance spawned by heterogeneity is adaptive, we might anticipate that future work will demonstrate that the production of heterogeneous sub-populations is itself under genetic selection and control. In fact, multiple recent reports already point in that direction ( Bellerose et al., 2019 ; Safi et al., 2019 ; Safi et al., 2020 ; Ma et al., 2021 ; Carey et al., 2022 ; Martini et al., 2022 ).…”
Section: Discussionmentioning
confidence: 96%
“…Recently, variant analysis, transcriptional studies and genome-wide transposon sequencing were used to unravel the biological basis of the distinctive phenotypes of Beijing strains. These analyses identified functional genetic changes across multiple stress and host response pathways, suggesting that these adaptive changes may be the reason for the distinct clinical characteristics and epidemiological success of this M. tuberculosis family [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, we have previously found that higher epidemiologic fitness of L2.2 strains correlates with slower growth in mice. 50 Therefore, we sought to assess the epidemiologic fitness of the L1 subclade strains. Terminal branch lengths (TBLs), determined by the number of SNPs derived from the most recent branching point of each strain, serves as a proxy for the maximum evolutionary time after transmission.…”
Section: Mtb L1 Clade Is Associated With Poor Clinical Outcomes and I...mentioning
confidence: 99%